Development and Validation of a German Language Unit-Level Organizational Citizenship Behavior (OCB) Scale - Gunnesch-Luca, George; Moser, Klaus (European Journal of Psychological Assessment, 2019)
The current paper presents the development and validation of a unit-level Organizational Citizenship Behavior (OCB) scale based on the referent-shift consensus model (RSCM). In Study 1, with 124 individuals measured twice, both an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA) established and confirmed a five-factor solution (helping behavior, sportsmanship, loyalty, civic virtue, conscientiousness). Test–retest reliabilities at a two-month interval were high (between .59 and .79 for the subscales, .83 for the total scale). In Study 2, unit-level OCB was analyzed in a sample of 129 work teams. Both interrater reliability measures (IRR) and interrater agreement values (IRA) provided support for RSCM requirements. Finally, unit-level OCB was associated with group task interdependence and was more predictable (by job satisfaction and integrity of the supervisor) than individual-level OCB in previous researc
Keywords: unit-level OCB; referrer-shift consensus model; job satisfaction; integrity; task interdependence